Voltage control strategies for offshore wind power collection systems upon faults - Fan, Y.; Ghosh, Arindam (2016)
Three types of offshore wind power collection topologies are studied for DC power systems in this paper. Permanent Magnet Synchronous Generator (PMSG) based Wind Energy Conversion System (WECS) is considered and the Optimal Power Control (OPC) is used for the Maximum Power Point Track (MPPT) control. The failure of a wind power unit is regarded as the fault condition in this paper. Voltage control strategies are proposed for series and series-parallel power collection topologies when such a fault happens. Input and output voltage references of the Grid-Side Converter (GSC) are modified for series power collection systems on fault conditions. For series-parallel collection systems, power switches are employed between wind power branches and different voltage control effects with different switch options are discussed. Simulation studies are conducted base on PSCAD/EMTDC to validate the proposed control strategies.